Analisis Pengaruh Celebrity Endorsement dan Price Perception terhadap Purchase Intention: Studi Kasus Pengguna Somethinc - Febryana Nawantoro; Indra Hastuti; Taufiq Nur Muftiyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to determine the influence of celebrity endorsement on Purchase Intention partially, to determine the influence of Price Perception on purchasing decisions, and to determine the influence of product quality and price determination on Purchase Intention, a case study of somethinc skincare users in Surakarta City simultaneously. The sample was 100 respondents using a sampling technique using random sampling. This research uses quantitative methods with SPSS 25 64 bit data analysis tools. Data analysis techniques in this research use validity tests, reliability tests, classical assumption tests, T tests, and F tests. The results of this study show that there is a positive and significant influence of celebrity endorsement on Purchase Intention, there is a positive and significant influence of Price Perception on Purchase Intention. . Then the research results concluded that simultaneously there was a positive and significant influence of celebrity endorsement and Price Perception on Purchase Intention.